Impact of logistic facilities and cost competitiveness on marketing activities of manufacturing SMEs (w.r.t. Mumbai and Thane) (International Journal of Food and Nutritional Sciences, 2023)
SMEs are backbone of Indian economy. They help in socio-economic development of the economy. They account for nearly 40% of total industrial output in India. Maharashtra has most number of SMEs in India, followed by Tamil Nadu, Uttar Pradesh. Gujarat and Rajasthan. Small Industries Development Bank of India (SIDBI) has been established in 1990, which acts as a regulatory body for SMEs. Indian SMEs face lot of problems relate to marketing of their products due to which they are unable to compete with multinationals, produce average quality products and have narrow customer base.From the literature review of over 50 literatures, it was found that that no study has been conducted on marketing problem faced by Manufacturing SMEs in Mumbai and Thane region. Also, no study has been conducted to study government schemes offered to MSMEs and the impact of the schemes on their business process. There is no study on non-financial factors affecting performance of SMEs in Maharashtra. Also, there is no study on financial innovation and financial flexibility of SMEs in Mumbai region.Objective of the study is to study different problems faced by SMEs in Mumbai and Thane in marketing of goods. They face different problems relating to access to credit, cost competitiveness, research and development activities, government support system, marketing problems and supply chain management.A Pilot Study has been conducted for over 100 SMEs and result of the study was obtained using IBM SPSS. Study was conducted on parameters like financing facilities, product development, cost competitiveness, marketing problem, government support and logistics facilities. Pilot Study was conducted by collecting questionnaires of responses from SMEs.The result of the study revealed that there is need to conduct study in this area.Manufacturing sector SMEs face lot of problems related to marketing of their products due to financial constraints. At the same time, they face problem in Research and development activity, which affect their marketing performance. Factors like financial constraints and product development, makes it difficult for SMEs to compete with large companies. Other factors that affect marketing activities of manufacturing SMEs are cost competitiveness, lack of government support and logistic facility. Hence, there is need to conduct study in this area and study problems faced by SMEs in Mumbai and Thane in marketing of goods.